Acceptability and feasibility of human papillomavirus vaccination for adolescents in school environments in Libreville - Ambounda, Nathalie L.; Woromogo, Sylvain H.; Kenmogne, Olive M.; Yagata Moussa, Felicite E.; Simo Tekem, Vicky N.; Ango, Eliane O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: High-risk oncogenic human papillomaviruses (HPV) are the cause of sexually transmitted viral infection. Its persistence is a risk factor for precancerous lesions of the cervix, which will constitute the base of cervical cancer. In the world, the prevalence of high-risk oncogenic HPV is 66.7%, which is higher among women starting their sexual activity. Methods: An analytical cross-sectional study was conducted in high schools in Gabon regarding parents. The variables selected were the socio-cultural and demographic characteristics of the parents, their knowledge of human papillomavirus vaccination and their acceptability of HPV vaccination and finally the feasibility of HPV vaccination. The statistical test used was Pearson's Chi-square, and a difference was considered significant for p<0.05. Results: The majority of parents, 89%, were informed of the existence of cervical cancer. However, 73.4% of them were unaware of the existence of vaccination against cervical cancer. Only 2.4% of parents had vaccinated their daughters against cervical cancer at the time of the study. These parents only 53.4% expressed an interest in vaccinating their daughters in 53.4% of cases. The ability to vaccinate children is associated with the socio-professional status of parents (p˂0.000). Conclusions: The majority of parents approved school-based vaccination against human papillomavirus infections despite its reported cost and lack of information. The integration of anti-HPV vaccination into the expanded programme on immunization in Gabon will improve immunization coverage.